Revisiting p38 Mitogen-Activated Protein Kinases (MAPK) in Inflammatory Arthritis: A Narrative of the Emergence of MAPK-Activated Protein Kinase Inhibitors (MK2i) - Payal Ganguly; Tom Macleod; Chi Wong; Mark Harland; Dennis McGonagle (Pharmaceuticals, 2023)
The p38 mitogen-activated protein kinase (p38-MAPK) is a crucial signaling pathway closely involved in several physiological and cellular functions, including cell cycle, apoptosis, gene expression, and responses to stress stimuli. It also plays a central role in inflammation and immunity. Owing to disparate p38-MAPK functions, it has thus far formed an elusive drug target with failed clinical trials in inflammatory diseases due to challenges including hepatotoxicity, cardiac toxicity, lack of efficacy, and tachyphylaxis, which is a brief initial improvement with rapid disease rebound. To overcome these limitations, downstream antagonism of the p38 pathway with a MAPK-activated protein kinase (MAPKAPK, also known as MK2) blockade has demonstrated the potential to abrogate inflammation without the prior recognized toxicities. Such MK2 inhibition (MK2i) is associated with robust suppression of key pro-inflammatory cytokines, including TNFα and IL-6 and others in experimental systems and in vitro. Considering this recent evidence regarding MK2i in inflammatory arthritis, we revisit the p38-MAPK pathway and discuss the literature encompassing the challenges of p38 inhibitors with a focus on this pathway. We then highlight how novel MK2i strategies, although encouraging in the pre-clinical arena, may either show evidence for efficacy or the lack of efficacy in emergent human trials data from different disease settings.